IDENTIFIKASI ALIH FUNGSI LAHAN PERTANIAN MENJADI NON-PERTANIAN (INDUSTRI) DI KABUPATEN CIANJUR SERTA DAMPAK BAGI PEREKONOMIAN MASYARAKAT WILAYAH SETEMPAT DI DESA SUKASIRNA KABUPATEN CIANJUR - Gustiwan, A.; Warlina, Lia (Universitas Komputer Indonesia (UNIKOM), 2019)
Sukasirna Village is one of ten villages that existed in Kecamatan Sukaluyu. The area of Kecamatan Sukaluyu is about 48.02 km2 or 4,802 ha. In the local Government Regulation No. 17 Year 2012 about Spatial Plan Kabupaten Cianjur in 2011 – 2031 set Kecamatan Sukaluyu bas set industrial zone. The research objectives area to identify land use change and it’s impact were to the economy of community in Desa Sukasirna. Data collection techniques were primary and secondary data collection. Primary data obtained from the results of observation and dissemination of questionnaires to the communities and farmers, while the secondary data obtained from relevant institutions agencies such as BAPPEDA, Badan Pusat Statistik, and the Office of Sukasirna Village. Method used for data analysis were descriptive analysis and overlay techniques for land use map in 2006, 2011, and 2016. The reseach resultan showed there was conversion of agricultural land into industrial land use. The area of agricultural land i.e ricefield in 2006 was 81.1 percent, in 2011 was 77 percent and in 2016, the area was 66.2 percent. The Langest conversion of agricultural land into industrial land was in 2011 to 2016 with an area of 57,37. The impact on livelihoods and people's income in 2016 had a decline in the number of farmers and there was an increasing livelihood of factory employees. The growth of industry increased the income of the community in 41 percent and additional income such as trading around the industrial area. Impacts on farmers led to a decrease in land ownership of farmers with a percentage of 48 percent, as well as other impacts on the environment were water pollution and air /sound pollution with a percentage of 70 percent. Kata Kunci : Guna Lahan, Perubahan Guna Lahan, Pemukiman, dan Pemasukan